Công văn của Bộ Xây dựng về việc trả lời chất vấn của Đại biểu Quốc hội tỉnh Gia Lai (Số: 604/BXD-HTKT) - Bộ Xây dựng (2018)
Công văn của Bộ Xây dựng về việc trả lời chất vấn của Đại biểu Quốc hội tỉnh Gia Lai (Số: 604/BXD-HTKT) ngày 27/3/2018